Angular Velocity, Moment, and Power Analysis of the Ankle, Knee, and Hip Joints in the Goalkeeper's Diving Save in Football - Ibrahim, Rony; Kingma, Idsart; de Boode, Vosse; Faber, Gert S.; van Dieën, Jaap H. (Frontiers in Sports and Active Living, 2020)
The aim of this study was to identify biomechanical characteristics of goalkeeper’s diving performance in football. Lower extremity joints powers, moments and angular velocities, were investigated in seven elite goalkeepers diving to save balls, shot from a ball canon to unanticipated heights (high and low) and sides (right and left). Our result showed that there was a proximal-to-distal sequence for each leg in timing of peak joints powers (p<0.05). Hip extensors produced the largest (p<0.05) peak moment, the contralateral (relative to dive side) peak was significantly larger than the ipsilateral one for high (4.56 ±1.02 N·m·kg-1, and 3.52 ±0.79 N·m·kg-1) and low dives (3.52 ±0.79 N·m·kg-1, and 2.52 ±0.56 N·m·kg-1). The ankle plantar flexors produced the second largest peak moment (p<0.05), and the peak ipsilateral ankle power and angular velocity were the largest (p<0.05) of all joints, during high (1502 ±338 W, and 14.73 ±1.36 rad·s-1) and low dives (868 ±263 W, and 14.14 ±3.09 rad·s-1). Strength and conditioning coaches need to focus on hip extensors and ankle plantar flexors, and for specificity in power training that should elicit triple extension of the lower limbs’ joints in a proximal-to-distal sequence.